2022-RA-1075-ESGO Long term follow-up and outcomes of borderline ovarian tumours – a ten year review of the south east wales gynaecological oncology centre (SEWGOC). (20th October 2022) - Zeinah, Hassan; Adama, Daniel; Tan, Elsie; Barclay, Upha; Jones, Sadie; Rzyska, Ewelina; Lim, Kenneth; Howells, Robert; Rowlands, Gareth; Sinha, Anju; Sharma, Aarti
Abstract : Introduction/Background: Borderline ovarian tumours (BOT) are low malignant potential tumours. There is no consensus on how best to follow up those patients. The aim of this service evaluation project is to assess our current management and long-term outcomes and follow up in women diagnosed with borderline ovarian tumours over a ten-year period. Methodology: All women with confirmed histological diagnosis of BOT who underwent primary surgery at SEWGOC between 1st January 2007 to 31st December 2016 were included. Retrospective review of patients' electronic medical records was undertaken. Information regarding FIGO stages, management (fertility preserving surgery/pelvic clearance), follow up and recurrence were analysed. Results: Seventy-nine patients were diagnosed with BOT. The mean age was 48 years (range 18 – 86). Of these, 67 were stage I, 4 stage II and 8 stage III. Fertility sparing surgery (mean age 38) was performed in 32 patients (30 stage I, 2 stage III). Of these, 22 had follow-up. Four of 32 (12.5%) had recurrences. Pelvic clearance (mean age 55) was undertaken in 47 patients. Of these, 23 had follow up. Three of 47 (6%) patients presented with recurrence. All recurred within 5 years. Conclusion: This evaluation shows that recurrence in women who undergo fertility sparing surgery is doubled versus pelvic clearance. All patients with recurrence presented with symptoms within 5 years of initial surgery. Symptom-led follow up could be a suitable modality especially in those who underwent pelvic clearance.